2013
DOI: 10.4021/jocmr1515w
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors That can Predict Antenatal Insulin Need in Gestational Diabetes

Abstract: BackgroundThis study was undertaken to assess the association between insulin need in gestational diabetes mellitus (GDM) and clinical features and laboratory parameters. Factors that can predict insulin need are also identified.MethodsCases with GDM were included retrospectively from records. Cases which failed to achieve target blood glucose levels with medical nutrition therapy (MNT) and need insulin treatment were recorded. Risk factors which can predict antenatal insulin treatment (AIT) were identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 24 publications
9
37
1
3
Order By: Relevance
“…Consistent with the current study, a number of other studies have identified clinical and biochemical variables associated with a need for insulin therapy in GDM [3][4][5][6][7][8][9][10][11][12]. The majority of these identified independent predictors of therapy type using multivariable logistic regression analysis [3][4][5][6][7][8][9]12].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Consistent with the current study, a number of other studies have identified clinical and biochemical variables associated with a need for insulin therapy in GDM [3][4][5][6][7][8][9][10][11][12]. The majority of these identified independent predictors of therapy type using multivariable logistic regression analysis [3][4][5][6][7][8][9]12].…”
Section: Discussionsupporting
confidence: 70%
“…The majority of these identified independent predictors of therapy type using multivariable logistic regression analysis [3][4][5][6][7][8][9]12]. Many identified the same predictors of insulin that were found in the present study, such as elevated pre-pregnancy BMI [4,5,8,9], elevated OGTT fasting glucose [3,4,6,8,9], elevated HbA 1c at GDM diagnosis [3,5,9], a history of GDM in a previous pregnancy [9], a family history of type 2 diabetes [3,5] and an earlier diagnosis of GDM [3,7,8].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The insulin group had a younger gestational age at diagnosis of gestational diabetes. Some studies have demonstrated that the fasting glucose level on OGTT [14][15][16][17] and the gestational week at diagnosis [14][15][16]18] are associated with the requirement for insulin therapy. The initial abnormality in glucose intolerance is postprandial hyperglycemia [13,19].…”
Section: Discussionmentioning
confidence: 98%